Polymorphism rs3733591 of the SLC2A9 gene and metabolic syndrome affect gout risk in Taiwan Biobank subjects - Lin, Chun-Nan; Ho, Chien-Chang; Hsieh, Pao-Chun; Hsiao, Chih-Hsuan; Nfor, Oswald Ndi; Liaw, Yung-Po (Frontiers in Genetics, 2024)
Background: Over the past few decades, gout and diseases like metabolic syndrome (MetS) have become more prevalent. Attempts have been made in Taiwan to identify the genes responsible for gout. A few gene loci, among them SLC2A9, have been identified using Taiwan Biobank (TWB) data. We, therefore, examined whether MetS could also account for the association between polymorphism SLC2A9 rs3733591 and gout.The final analysis consisted of 73,558 subjects, of whom 2,709 had gout. To estimate the likelihood of gout occurrence based on rs3733591 and MetS, we used logistic regression models.Results: Rs3733591-TC+CC compared to TT genotype was associated with gout (OR, 1.15; 95% CI, 1.06 to 1.25). Also associated with gout was MetS (OR, 1.21; 95% CI, 1.10 to 1.33). A significant interaction was seen between rs3733591 and MetS (p-value = 0.039). Using rs3733591-TT/no MetS as the reference group, the ORs (95% CI) for gout was 1.24 (1.11 to 1.38) for TC+CC/no MetS, 1.35 (1.17 to 1.56) for TT/MetS, and 1.39(1.22 to 1.58) for TC+CC/MetS. However, subgroup analysis defined by sex showed no significant associations in women.In summary, metabolic syndrome and SLC2A9 rs3733591 genotypes were interactively associated with gout in Taiwanese men, but not women.